Pengembangan Media Pembelajaran Berbentuk Lemari Lipat Pada Pelajaran IPAS Di Kelas IV SD Negeri 224 Palembang - Maharani Putri, Dian; Bambang; Imelda (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the validity, practicality and effectiveness of the folding cupboard learning media in the fourth grade science lesson of SD Negeri 224 Palembang. The subjects of this study were the fourth grade of SD Negeri 224 Palembang. Data collection techniques in this study used student and teacher response sheets, pretest posttest question sheets and validator sheets. The results of this study indicate that the pretest results with a minimum value of 25 and a maximum value of 90 with an average value of 54.46 with fairly effective criteria. Posttest results with a minimum of 50 and a maximum of 100 with an average value of 76.42. While the normality test, homogeneity test, validity test, reliability test, and level of difficulty were tested with SPSS version 25.